Character Education Development Pattern: Efforts to Empower School Managers - Arif Wahyudi (Al-Hayat Al-Istiqomah Foundation, 2018)
Character education is a good thing. In Islam, characters are identical with morality, namely the tendency of the soul to behave automatically. The righteousness that is by Islamic teachings is called the ultimate morality or noble morality. The purpose of this study was to analyze the patterns, implementation, and implications of character education in private Islamic education institutions in remote districts. The research method uses the interpretive paradigm through a qualitative approach, the type of case study. The analytical tool used is a qualitative analysis model of Miles and Huberman. The results of this study are character education patterns through habituation of habituation and habituation in learning, exemplary teacher, employees and leaders, and board administrators and a system of punishment and appreciation and communication has accommodated the ideal character education pattern. The implementation of character education has both involved the community so that the synergy between all elements and evaluations is done at the end of the year. The implications of character education on the role of parents or guardians are less significant; the perception of the people who have not changed has left all responsibilities to schools unattended outside the school. Pendidikan karakter adalah sesuatu yang baik. Dalam Islam, karakter identik dengan akhlaq, yaitu kecenderungan jiwa untuk bersikap secara otomatis. akhlaq yang sesuai ajaran Islam disebut dengan akhlaqul karimah atau akhlaq mulia. Tujuan penelitian ini adalah untuk menganalisis pola, implementasi dan implikasi pendidikan karakter di lembaga pendidikan Islam swasta di daerah kabupaten terpencil. Metode penelitian menggunakan paradigma interpretif melalui pendekatan kualitatif, jenis studi kasus. Alat analisis yang digunakan adalah model analisis kualitatif Miles dan Huberman. Hasil dari penelitian ini adalah pola pendidikan karakter melalui pembiasaan ubudiyah dan pembiasaan dalam pembelajaran, keteladanan guru, karyawan dan pimpinan serta pengurus pondok dan sistem hukuman dan penghargaan serta komunikasi sudah mengakomodir pola pendidikan karakter yang ideal. Implementasi pendidikan karakter sudah baik melibatkan masyarakat sehingga sinergi antar semua elemen dan evaluasi di lakukan pada akhir tahun. Implikasi pendidikan karakter pada peran orang tua atau wali yang kurang signifikan, persepsi masyarakat yang masih belum berubah menyerahkan semua tanggung jawab ke sekolah tanpa pengawasan di luar sekolah.